The Role of Brand Recognition in Enhancing Customer Retention in the Pharmaceutical Retail Sector of Zimbabwe: A Case Study of Pharmacies in Chinhoyi, Mash West, Zimbabwe - Munyoro, Gerald; Madzinga-Kusena, Priscilla (British Journal of Healthcare and Medical Research, 2024)
This study was based on the role of brand recognition in enhancing customer retention in the pharmaceutical retail sector of Zimbabwe because brand recognition and customer retention have become popular subjects in recent years since it is believed that customers are the life blood of any business. Accordingly, the study made use of self –administered questionnaires in collecting data from customers and employees of retail pharmacies in Chinhoyi, Mash West province in Zimbabwe and the respondents were selected through stratified random sampling. Consequently, the data was analysed qualitatively using thematic analysis supported by quantitative analysis to make sure the results were genuine. Therefore, the research findings show that brand recognition does not exist in the pharmaceutical retail sector in Zimbabwe even though the majority of respondents agreed that branding especially brand recognition plays a significant role in shaping customer loyalty as well as customer retention. Furthermore, the study also shows that the attributes of branding includes familiarity with brand, relevance of pharmacy brand, differentiation of pharmacy brand, perceived quality of a brand, reliability and esteem of a brand are positive influencers of customer loyalty by so doing enhancing customer retention.